Factors associated with functional recovery in Japanese patients with convalescent stroke stratified by age: a multicenter observational study. Issue 3 (September 2019) - Kimura, Yosuke; Ohji, Shunsuke; Ishiyama, Daisuke; Nishio, Naohito; Otobe, Yuhei; Suzuki, Mizue; Ogawa, Hideyuki; Ichikawa, Takeo; Taguchi, Ryota; Shino, Shuhei; Tanaka, Shu; Yamada, Minoru
Abstract : Factors associated with functional recovery after stroke may differ by age demographics because the aging process leads to various regressive changes. The aim of this study was to identify factors related to functional recovery in Japanese patients with convalescent stroke stratified by age. A multicenter retrospective observational study was conducted in 243 patients from six convalescent inpatient rehabilitation wards. Participants were categorized into three groups: 40–64, 65–74, and ≥75 years. Demographic data, laboratory data, physical function, and cognitive function were collected upon admission, and outcome measures were represented using the relative gain of the Functional Independence Measure (FIM effectiveness) during hospitalization. Stepwise multivariate logistic analysis was performed to identify the significant factors for functional recovery in each group. In the 40–64 years group, stroke type [odds ratio (OR), 10.38; 95% confidence interval (CI), 2.22–48.59], spatial neglect (OR, 7.61; 95% CI, 2.07–28.00), and memory disorder (OR, 4.68; 95% CI, 1.08–20.30) were shown to be significant factors. In the 65–74 years group, only memory disorder (OR, 3.42; 95% CI, 1.19–9.81) was significant. In the ≥75 years group, low albumin level (OR, 3.35; 95% CI, 1.05–10.67), severe motor impairment (OR, 5.11; 95% CI, 1.14–22.97), and memory disorder (OR, 4.34; 95% CI, 1.43–13.23) were significantly related to poor functional recovery. In conclusions, the findings showed that there were different trends among the factors related to poststroke functional recovery among the three age groups.